Growth and metastasis of lung adenocarcinoma is potentiated by BMP4-mediated immunosuppression. (1st November 2016) - Chen, Limo; Yi, Xiaohui; Goswami, Sangeeta; Ahn, Young-Ho; Roybal, Jonathon D.; Yang, Yongbin; Diao, Lixia; Peng, Di; Peng, David; Fradette, Jared J.; Wang, Jing; Byers, Lauren A.; et al.
ABSTRACT: Cancer cells modulate the recruitment and function of inflammatory cells to create an immunosuppressive microenvironment that favors tumor growth and metastasis. However, the tumor-derived regulatory programs that promote intratumoral immunosuppression remain poorly defined. Here, we show in a Kras LA1/+ p53 R172HΔg/+ -based mouse model that bone morphogenetic protein-4 (BMP4) augments the expression of the T cell co-inhibitory receptor ligand PD-L1 in the mesenchymal subset of lung cancer cells, leading to profound CD8 + T cell-mediated immunosuppression, producing tumor growth and metastasis. We previously reported in this model that BMP4 functions as a pro-tumorigenic factor regulated by miR-200 via GATA4/6. Thus, BMP4‐mediated immunosuppression is part of a larger miR‐200‐directed gene expression program in tumors that promotes tumor progression, which could have important implications for cancer treatment.